Research Trends in Thermal Therapy and Wearable Devices for Hypertension Management: A Bibliometric Analysis - Sehat Dwi Prasaja; Rusana Rusana; Saryono Saryono (Media Keperawatan Indonesia, 2025)
Hypertension remains a major global health issue, contributing substantially to cardiovascular morbidity and mortality. While pharmacological treatment is well established, interest in non-pharmacological interventions such as heat therapy and wearable heating devices including thermal footwear has increased. However, the research landscape on these interventions has not been systematically examined. This study analyzed global research trends on heat therapy and hypertension from 2000 to 2025 using bibliometric methods, emphasizing wearable technologies. Scopus-indexed publications were identified following PRISMA 2020 guidelines. A total of 133 studies met inclusion criteria. Bibliometric indicators were analyzed using VOSviewer to assess publication growth, major contributors, collaboration networks, co-citation, and keyword co-occurrence, supported by visualization maps. Research output increased steadily, peaking with 20 publications in 2025. Three thematic clusters were identified: population health, physiological function, and thermal/vascular interventions, showing a shift toward focused physiological and interventional research. Wearable heating devices remain underrepresented in the literature, indicating a research gap and highlighting their potential for future hypertension management.